Great Firewall baseline (China) - Voidly (Voidly Global Censorship Index, 2017)
CRITICAL severity censorship detected in China. Data sourced from OONI, CensoredPlanet.
Censorship Incident ID: CN-2017-0001. Severity: critical. Confidence: 95%